Analisis Rasio Profitabilitas untuk Menilai Kinerja Keuangan PT Indofarma (Persero), Tbk - Santa Maria Manungkalit; Dimas Sumitra Danisworo; Banter Laksana (Indonesian Journal of Economics and Management, 2022)
This study aims to analyze the financial performance of PT. Indofarma, Tbk using the profitability ratio approach. Performance research variables use profitability ratios which include Return on Asset Ratio (ROA), Return on Equity Ratio (ROE), and Net Profit Margin (NPM). The method in this study uses quantitative research with a descriptive approach. The focus of this research includes how the profitability ratio analysis can show the financial performance of PT.Indofarma from 2016 to 2020. Based on the results of the company's financial data processing, seen from the company's Return on Assets , it can be concluded that the company's financial performance is not good and the company is less effective in using assets. his. Based on Return on Equity from 2016 to 2020 can seen that the company's financial performance is not good because it is still below the industry standard of 40%. And the value of the Net Profit Margin is said to be still not good because it has not met the industry standard average of 20%. Overall, the financial performance of PT. Indofarma for the last 5 years is not good when compared to industry standards. However, in 2019 and 2020, the company began to increase its sales so that the company's financial performance began to improve even though it was still far from the industry average.